Implementation of Islamic Religious Education in Farmer Families for Early Childhood - Agustinah Agustinah; Leli Fertiliana Dea; Yuning Eka Rahma Wati (Bulletin of Early Childhood, 2025)
Early childhood, especially at the age of 5-6 years, is at a very important developmental stage in the formation of character, personality, and religious values, so that Islamic religious education in the family is very crucial as the initial foundation of a child's life. However, the professional background of parents, such as plantation families, influences the pattern and intensity of the implementation of religious education at home due to time constraints due to high work activities. This study aims to describe the implementation of Islamic religious education in plantation families for early childhood at RA Nurul Muttaqin Penumangan Baru, Tulang Bawang Tengah District, West Tulang Bawang Regency in the 2025/2026 Academic Year. This study uses a qualitative descriptive approach with a type of field research, with research subjects determined through a purposive sampling technique, namely plantation parents and children aged 5-6 years. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of Islamic religious education in plantation families is carried out flexibly but meaningfully through the method of role models (uswah hasanah), habituation of worship, dialogue and value development, as well as simple supervision and evaluation, despite being limited by time and busy parents. In addition, a conducive home environment and support from schools and social environments also strengthen the internalization of Islamic values in children, as shown by indicators such as knowing religion, carrying out worship, understanding moral values, cultivating good manners, maintaining cleanliness, recognizing Islamic holidays, fostering an attitude of tolerance, and internalizing spiritual values. Thus, Islamic religious education in plantation families not only functions as a transfer of knowledge, but is also effective in shaping children's religious character as a whole from an early age.